Ignition stability of hydrogen in noble gases atmosphere in compression ignition engine - Norhidayah Mat Taib,; Wan Mohd Faizal Wan Mahmood,; Hasan Koten,; Mohd Radzi Abu Mansor, (Fakulti Kejuruteraan ,UKM,Bangi., 2023)
Hydrogen fuel promises a high engine efficiency and the ability to eliminate harmful emissions in an internal combustion engine. However, the ignition stability of hydrogen in compression ignition engine is unstable due to the high-auto ignition temperature of hydrogen. Noble gases such as argon, krypton and xenon have a larger molecular weight compared to nitrogen. Therefore, replacing nitrogen with noble gases appears to be a promising option due to their high specific heat ratio. This paper aims to investigate the ignition stability in a heavy molecular noble gases atmosphere in a CI engine. In this study, Converge CFD software simulates a single-cylinder compression ignition engine model based on the Yanmar NF19SK engine parameters. Hydrogen combustion in a noble gas atmosphere resulted in low ignition stability when operated at low intake temperature. Based on this study, we found that increasing intake temperature improves the ignition stability. As a result, argon is the most preferable among other noble gases. Nevertheless, future research should investigate the other noble gases’ capability under different parameters to improve the engine’s thermal efficiency.